2019
DOI: 10.14349/rlp.2019.v51.n2.4
|View full text |Cite
|
Sign up to set email alerts
|

Profile and neuropsychological differences in adolescent students with and without dyslexia

Abstract: Dyslexia is a problem of increasing prevalence in school-age students. The latest experiences in the application of neuropsychology to education are interesting because they allow for the evaluation of different neuropsychological variables to obtain a better understanding of the learning processes of students in this population for specific subsequent interventions. The purpose of this study was to explore the following neuropsychological variables related to reading in adolescent students with and without dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…In addition to these domain-specific hypotheses, others have proposed that ALD may be secondary to deficits in domain-general processes, such as executive functions, working memory (WM), and intellectual capacity. Several studies have reported deficits in WM in children with ALD (and also in children with reading disabilities), both when assessing verbal WM with digit span, and when using visuo-spatial span tasks (Aragón et al, 2019;Barnes et al, 2020;Castro et al, 2017;Guzmán et al, 2019;Ibáñez-Azorín et al, 2019).…”
mentioning
confidence: 99%
“…In addition to these domain-specific hypotheses, others have proposed that ALD may be secondary to deficits in domain-general processes, such as executive functions, working memory (WM), and intellectual capacity. Several studies have reported deficits in WM in children with ALD (and also in children with reading disabilities), both when assessing verbal WM with digit span, and when using visuo-spatial span tasks (Aragón et al, 2019;Barnes et al, 2020;Castro et al, 2017;Guzmán et al, 2019;Ibáñez-Azorín et al, 2019).…”
mentioning
confidence: 99%